Pengaruh Kesehatan Mental Dan Konflik Kerja Terhadap Kinerja Pegawai Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada Dinas Perhubungan Provinsi Sumatera Barat - Hamdi, Miftahul; Kumbara, Vicky Brama; Candana, Dori Mittra (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
This study aims to determine and analyze the influence of mental health and work-related conflict on employee performance, with job satisfaction as an intervening variable at the West Sumatra Provincial Transportation Agency. This study used Structural Equation Modeling (SEM) with SmartPLS 3.0 as the analysis tool. The population and sample were 76 West Sumatra Provincial Transportation Agency employees. Data collection was conducted by distributing questionnaires to West Sumatra Provincial Transportation Agency employees who had worked directly at the agency.  The results showed a positive and insignificant effect between Mental Health and Job Satisfaction. There was a positive and insignificant effect between Work-related Conflict and Job Satisfaction. There was a positive and significant effect between Mental Health and Employee Performance. There was a positive and significant effect between Work-related Conflict and Employee Performance. There was a negative and significant effect between Job Satisfaction and Employee Performance. Job Satisfaction did not mediate the effect of Mental Health on employee performance. Job Satisfaction did not mediate the effect of Work-related Conflict on Employee Performance.